PREVALENSI DEPRESI DAN GAMBARAN STRESSOR PSIKOLOSOSIAL PADA REMAJA SEKOLAH MENENGAH UMUM DI WILAYAH KOTAMADYA MALANG - Asmika, Asmika; Harijanto, Harijanto; Handayani, Nina (Fakultas Kedokteran Universitas Brawijaya, 2008)
During the mental development process, the adolescent will be exposed tonumerous events that might act as psychosocial stressors. These stressors might contribute to the prevalence of depression in adolescent. This study aimed to determine the prevalence of depression description of psychosocial stressor, and the relationship between psychosocial stressors and depression in adolescent. A cross sectional descriptive analytic study was conducted using 458 particiapants from three representative Senior High Schools in Malang district. The depression level was measured using Beck Depression Inventory while Holmes and Rahe Stress Scale for Youth was used to mesure the level of psychosocial stressor. It was found that prevalence of depression were as follows 32,5% of respondents with mild depression; 28,2% with moderate depression; and the remaining 11,1% withsevere depression. Of all particiapants, 59,6% experience a high level stressor, while the other 40,4% have low level stressor. The study identify a significant correlation (p<0.001)between depression level and level of psychosocial stressor. . The risk of having depression is 5.87 higher in respondents with high level of psychosocial stressor compare to those with low level psychosocial stressor (OR=5.87). Therefore, a cooperation between school, community and parent is highly advised toprovide a favourable environment for mental development in adolescent. In addition parents, school need to prepare the adolescent in order to anticipate numeros events that influence their mental health.